Perception of parents of children admitted to the Intensive Care Unit about the Unit's routines (Research, Society and Development, 2020)
Objective: to describe the perception of parents of children admitted to the Intensive Care Unit about the unit's routines. Methodology: This is an integrative literature review of literature carried out in the following databases / databases: Science direct, National Library of Medicine National Institutes of Health of the USA (PUBMED), Latin American and Caribbean Literature in Health Sciences (LILACS) and Medical Literature Analysis and Retrieval System Online (MEDLINE). Subsequently, the material was processed by the Iramuteq software, using Reinert's analysis. Result: The total number of articles found in the review were 24 articles, which after analyzed emerged the following themes: The Intensive Care Unit as an environment not understood by the caregivers of children admitted to the unit; The lack of information about the child's environment and clinical condition to relatives; The importance of means that subside and improve communication between professionals and parents. Conclusion: Family members described the ICU as a place with excessive standards and procedures where the multiprofessional team often does not describe what the parents' functions are in the unit.